تحري نقص السمع عند الأطفال بقياس المعاوقة السمعية - إبراهيم, مصطفى; الرستم, محمد; سليمان, رنا (Latakia University Journal -Medical Sciences Series, 2019)
إن تحري نقص السمع عند أطفال المدارس مهم جداً، لأن التهاب الأذن الوسطى المصلي يحدث بشكل متكرر في هذا العمر، مسبباً نقصاً متفاوتاً في السمع والذي بدوره له دور سلبي على استيعاب الأطفال وتركيزهم وفهمهم في سن المدرسة. إن قياس المعاوقة السمعية هو تقنية حساسة لاكتشاف إمراضيات الأذن الوسطى[1،2]. شملت هذه الدراسة 1500 طفل بعمر 3-9 سنوات بين عامي 2006-2007. مخطط الطبلة كان غير طبيعي في 92 حالة, أي بنسبة 6.13%، وكان نموذج C بنسبة 39.13%. كانت ضخامة الناميات هي العامل المسبب في أكثرمن نصف الحالات بنسبة 67.39%. Screening hearing of school – aged children is very important, because otitis media with effusion frequently occurs at this age, causing uneven hearing loss, which in turn has a negative impact on the understanding ability of children, their performance and concentration in school - age. Acoustic impedance test is a sensitive technique for detection of middle – ear pathologies[1،2]. This study includes 1500 children mean age 3-9 years, between 2006-2007. Tympanometry was abnormal in 92 cases at rate of 6.13%, and was type C at rate of 39.13%. Adenoid hyperplasia was the cause of more than half of the cases at rate of 67.39%.